A Simple Method for Determining the Critical Point of the Soil Water Retention Curve. Issue 2 (20th April 2017) - Chen, Chong; Hu, Kelin; Ren, Tusheng; Liang, Yin; Arthur, Emmanuel
Abstract : Core Ideas: A fixed tangent line method was developed to estimate the critical point of the soil water retention curve as an alternative to the commonly used flexible tangent line method. The critical points of the soil water retention curve from the proposed method and the flexible tangent line method were compared. Particle‐size distribution and specific surface area had significant effects on the critical point of the soil water retention curve. The transition point between capillary water and adsorbed water, which is the critical point P c [defined by the critical matric potential (ψc ) and the critical water content (θc )] of the soil water retention curve (SWRC), demarcates the energy and water content region where flow is dominated by capillarity or liquid film flow. Accurate estimation of P c is crucial for modeling water movement in the vadose zone. By modeling the dry‐end (matric potential < –10 4.2 cm H2 O) and wet‐end (matric potential > –10 4.2 cm H2 O) sections of the SWRC using the models of Campbell and Shiozawa, and of van Genuchten, a fixed tangent line method was developed to estimate P c as an alternative to the commonly used flexible tangent line method. The relationships between P c, and particle‐size distribution and specific surface area (SSA) were analyzed. For 27 soils with various textures, the mean RMSE of water content from the fixed tangent line method was 0.007 g g –1, which was slightly better than that of the flexible tangent line method. With increasing clay content or SSA, ψc was more negative initially but became less negative at clay contents above ∼30%. Increasing the silt contents resulted in more negative ψc values, whereas soils with higher sand content had less negative ψc values. The magnitude of θc increased linearly with SSA and clay content. Our findings suggest that P c estimated from the fixed tangent line method could represent the actual values and clarify the effect of particle‐size distribution and SSA on P c .